Implementation of Banking Service System to Improve Customer Satisfaction at PT Bank Rakyat Indonesia (PERSERO) Tbk KC Panyabungan - Rukiah Rukiah; Ummi Ismaya Sari; Ismed Sofyan (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to analyze the implementation of the banking service system to improve customer satisfaction at PT Bank Rakyat Indonesia (Persero) Tbk's Panyabungan Branch Office in Mandailing Natal Regency. This study used a qualitative approach with descriptive methods to obtain an in-depth overview of the bank's service system and customer perceptions of the quality of service provided. Data collection techniques included direct observation, interviews with customers and bank officers, and documentation related to banking services. The results indicate that the implementation of the banking service system at BRI Panyabungan Branch Office has generally been running well. Services provided to customers include teller services, customer service, and technology-based services such as ATMs and mobile banking. This service system is designed to provide ease and convenience for customers in conducting various banking transactions. The quality of service provided by the bank can be analyzed based on the service quality dimensions in the SERVQUAL model, which include tangibles, reliability, responsiveness, assurance, and empathy. Based on the results, most customers considered the service provided by bank officers to be quite satisfactory, particularly in terms of staff friendliness, clarity of information provided, and available service facilities. However, this study also identified several challenges in the implementation of the banking service system, such as long customer queues at certain times, limited service staff during busy times, and technical disruptions to the banking network. Therefore, efforts are needed to continuously improve service quality by enhancing human resource competency and optimizing service technology.